An archaeology of structural violence : life in a twentieth-century coal town - Roller, Michael (Cultural heritage studies., 2018)
An Archaeology of Structural Violence: Life in a Twentieth-Century Coal Town addresses topics such as the approach to the structural violence of everyday life in the twentieth century, the relationship between migrants and the sovereignty of political states, racialization, and the labor needs of late industrial capitalism.